2020
DOI: 10.3390/ijerph17238924
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Cancer Screening and Human Papillomavirus Vaccination among Korean Sexual Minority Women by Sex of Their Sexual Partners

Abstract: Cervical cancer-preventive behaviors in Korean sexual minority women (SMW) are underexplored. We aimed to assess the differences in cervical cancer screening uptake and completion of human papillomavirus (HPV) vaccination among Korean SMW by sex of their sexual partners. This cross-sectional study used data from the 2017 Korean Sexual Minority Women’s Health Study; we included Korean lesbian and bisexual women aged ≥20 years. They were divided into three groups: SMW with more than one male sexual partner (male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Several studies have confirmed that lesbians and women with only AFAB partners tend to perceive themselves as less likely to acquire HPV than bisexual women and (AMAB) [4,[40][41][42]. Moreover, studies have shown that SMW who have sex with bisexual women and AFAB individuals who have AMAB partners have a notable HPV risk factor [43].…”
Section: Hpv Transmissionmentioning
confidence: 95%
“…Several studies have confirmed that lesbians and women with only AFAB partners tend to perceive themselves as less likely to acquire HPV than bisexual women and (AMAB) [4,[40][41][42]. Moreover, studies have shown that SMW who have sex with bisexual women and AFAB individuals who have AMAB partners have a notable HPV risk factor [43].…”
Section: Hpv Transmissionmentioning
confidence: 95%
“…Among all women, these psychological variables were positively associated with never obtaining a Pap test and concealment was also negatively associated with clinical breast exam adherence. Kim, Lee & Choi-Kwon (43) Cervical cancer screening and human papillomavirus vaccination among Korean sexual minority women by sex of their sexual partners Descriptive 671 women LBW with only female partners had lower rates of Pap testing and completion of HPV vaccine than women with male and female partners.…”
Section: Sample Size Resultsmentioning
confidence: 99%
“…a short training session with a lesbian doctor, it was found that one in four women (58-66 years) who did not have a Pap test had a Pap test within 3 years. (1) Similarly, in the studies of Kim et al (43) it was found that LBW with only female partners had lower rates of Pap testing and completion of HPV vaccine than women with male and female partners.…”
Section: Breast Cancermentioning
confidence: 92%
“…In one study, 28% of sexual minority patients perceived that cervical cancer screening was unnecessary [ 81 ]. Compared to sexual minority patients with male partners, those with only female partners are less likely to have cervical screening [ 82 ]. In a survey of young bisexual and lesbian women, 30% of respondents had not had a Pap smear in the preceding 3 years [ 83 ].…”
Section: Resultsmentioning
confidence: 99%
“…The increased risk of CIN3+ in the former study is likely attributable to underscreening. In addition, fewer sexual minority patients undergo HPV vaccination [ 82 , 88 , 89 ]. Reported rates of smoking are also higher in the LGBTQ2S+ community, which is a known risk factor for the progression of HPV-related infections to cervical cancer [ 90 ].…”
Section: Resultsmentioning
confidence: 99%